Effects of co-composting of faecal sludge and agricultural wastes on tomato transplant and growth - Nartey, Eric Gbenatey; Amoah, Philip; Ofosu-Budu, G.K.; Muspratt, A.; Pradhan, Surendra K. (Springer, 2017)
Purpose: Faecal sludge (FS) has been co-composted with many organic solid wastes globally. Agricultural wastes, such as oil palm empty fruit bunches (EFB) and cocoa pod husks (CPH), have received very little research attention as far as combining with FS is concerned. This study aimed at co-composting these wastes at different ratios to produce safe compost for use as soilless medium for raising tomato transplants. Methods: Dewatered FS (DFS) was mixed with shredded EFB and CPH at five different ratios: 1DFS:1EFB, 1DFS:1CPH, and DFS:EFB:CPH in ratios of 1:1:1, 2:1:1, and 2:2:1 and composted for 3 months. Select physicochemical parameters and pathogens were monitored every fortnightly and 3 weeks, respectively. Results: Maximum temperatures obtained ranged 46.8–54.5 °C. Though these temperatures were lower than sanitizing temperatures prescribed by USEPA, no E. coli was found in any of the piles at the end of composting. The ratio 2DFS:2EFB:1CPH was found to be the safest formulation and hence was used to grow tomato under greenhouse conditions. Tomato seeds were sown in three different growing media: 100% FS-based compost, 100% rice husk biochar, and 50% FS-based compost–50% rice husk biochar mix. Conclusion: Results showed that FS-based compost was a suitable growing medium for tomato. Further studies into the optimal rate and frequency of application of compost teas on tomato are recommended.